Proliferative and genotoxic effect of Perivitelline fluid from horseshoe crab on human dental pulp stem cells - Thirumulu Ponnuraj, Kannan; Musa, Marahaini; Mohd Ali, Khadijah; Ahmad , Azlina; Omar, Nor Shamsuria; Chatterji, Anil; Mokhtar@Makhtar, Khairani Idah (2015)
The aim of this study was to evaluate the effect of perivitelline fluid (PVF) on the proliferation, chromosome aberration and mutagenicity of dental pulp stem cells (DPSCs). Crude extracts were prepared from the PVF collected from horseshoe crabs. For cytotoxicity test (MTT assay), the DPSCs were subjected to different concentrations of PVF crude extract. Two inhibitory concentrations (IC50=26.887mg/ ml and IC25=14.093mg/ml) and two other concentrations (0.278mg/ml and 0.019mg/ ml) which produced higher cell viability were selected for downstream experiments. The proliferative effect was assessed using AlamarBlue® assay for a period of 10 days and the population doubling time (PDT) were also calculated based on this assay. Chromosome aberration and Ames tests were employed for the evaluating the genotoxicity. Statistical analysis was carried out using independent t-test to assess the significant differences (p<0.05). AlamarBlue® assay showed that PVF groups produced comparable proliferation activity to negative (untreated) control. The PDTs between PVF groups and negative control were also insignificantly different (p>0.05). Both the chromosome aberration test and Ames test did not show any significant differences in the PVF treated groups. Hence, it can be concluded that PVF from horseshoe crabs produced insignificant proliferative activity and was non-genotoxic on DPSCs based on chromosome aberration and Ames tests.